IMPACT OF SEASONAL VARIATION ON ARBUSCULAR MYCORRHIZAL FUNGI IN LOWER HIMALAYA - REENU KUMARI; SUNIL PURI; MAMTA SHARMA (International Journal of Pharma and Bio Sciences, 2015)
Arbuscular mycorrhizal fungi (AMF) are associated with almost all plants in nature and are ubiquitous. The arbuscular mycorrhizal fungi status of 10 wild herb and shrub was investigated during winter and summer season in Pine forest of himalaya(HP). The herbs and shrubs investigated for studied are: Reinwardtia indica, Berberis lycium, Viola serpens,Taraxacum officinale, Caryopteris wallichiana, Indigofera pulchella, Rumex hastatus, Colebrookea oppositifolia, Leucas lantata and Verbascum thapsus. The result indicated that in all the ten selected wild herb and shrub Arbuscular mycorrhizal fungi (AMF) were observed in both winter and summer season. In the present study, the percentage of AMF root colonization was less in summer and higher in winter season. Similarly the highest number of AMF spore was found in winter and least in summer. In winter season, the maximum percent root colonization of AM fungi was observed in Verbascum thapsus (83.33±4.17) while minimum inIndigofera pulchella (45.83±4.17). The maximum AMF spore count from 50g rhizosphere soilwas observed in Indigofera pulchella (744.67±2.67) while minimum in Leucas lantata(254.67±2.40). In summer season, the percent root colonization of AM fungi was observed equal in Reinwardtia indica (58.33±4.17), Berberis lycium (58.33±4.17), Viola serpens (58.33±4.17),Leucas lantata (58.33±4.17). It was minimum in Caryopteris wallichiana (33.33±4.17).Maximum AMF spore counts from 50g rhizosphere soil were observed in Taraxacum officinale(543±2.64) while minimum in Leucas lantata (153.67±1.85). A total of 25 AMF species were isolated which belonged to five genera, i.e., Glomus, Acaulospora, Gigaspora, Endogone andDentiscutatas in both winter and summer seasons. Glomus was reported to be dominant generafollowed by Acaulospora in winter and summer seasons.Results showed area as a rich source of varied arbuscular mycorrhizal fungi.